THE EFFECT OF DIFFERENT LEARNING MODELS ON STUDENTS' SCIENTIFIC ATTITUDES AND CRITICAL THINKING SKILLS - Anang Setyobudi; Didimus Tanah Boleng; Sonja VT Lumowa (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2021)
This research aims to analyze (1) the influence of SETS and Contextual learning models on the Scientific Attitudes of students of class XI SMK Negeri 1 Telen and SMK Negeri 2 Bengalon, and (2) the influence of sets and contextual learning models on the critical thinking skills of students of class XI SMK Negeri 1 Telen and SMK Negeri 2 Bengalon, (3) the influence of sets and contextual learning models on scientific attitudes and critical thinking skills of students of class XI SMK Negeri 1 Telen and SMK Negeri 2 Bengalon simultaneously. The hypotheses tested were: (1) SETS and Contextual learning models affect the Scientific Attitudes of students of class XI SMK Negeri 1 Telen and SMK Negeri 2 Bengaland on, (2) SETS and Contextual learning models have an effect on the critical thinking skills of students of class XI SMK Negeri 1 Telen and SMK Negeri 2 Bengalon, (3) sets and contextual learning models affect scientific attitudes and critical thinking skills of students of class XI SMK Negeri 1 Telen and SMK Negeri 2 Bengalon Simultaneously. This type of research includes Quasi-Experimental Design. The target population is all students of class XI SMK Negeri 1 Telen and SMK Negeri 2 Bengalon Year of Study 2021/2022, the number of research samples as many as 77 students. Research instruments use scientific attitude questionnaires and tests of critical thinking skills. Research data were analyzed using MANCOVA's One Way statistical test. The results showed that: (1) There was no effect of sets and contextual learning model on the scientific attitude of students of class XI of SmK Negeri 1 Telen and SMK Negeri 2 Bengalon with partial eta squared value p2 = 0.3%. (2) There is an influence of sets and contextual learning models on the critical thinking skills of students of class XI SMK Negeri 1 Telen and SMK Negeri 2 Bengalon with partial eta squared values p2 = 86.61%, and (3) There is an influence of sets learning model and on scientific attitudes and critical thinking skills of students of class XI SMK Negeri 1 Telen and SMK Negeri 2 Bengalon simultaneously with partial value eta squared p2 = 76.90%.